Immune thrombocytopenia at the patient with a cystadenoma of the ovaries (а clinical case) - N. A. Pluzhnikova; V. E. Gruzdev; T. E. Byalik; E. A. Mustafina; T. V. Davydova; P. A. Zeinalova; Z. S. Shikhabova (Онкогематология, 2020)
Immune thrombocytopenia is an immunosuppressed acquired disease characterized by low platelet levels in peripheral blood and an increased risk of bleeding. This pathology deserves special attention in cases of patients who are scheduled for surgery, which undoubtedly requires careful preparation of the patient for surgery and a complete laboratory analysis, including a thromboelastogram.This article describes the clinical case of successful surgical treatment of a patient with immune thrombocytopenia.